Pain Management in Elderly with Herniated Disc: Exploring NSAID Options for Non-Surgical Treatment - Pratama, Alfath Bagus; Nasution, Luthfi Umam Hakim; Pane, Baharudin Yusuf; Perdana, Muhammad Agung; Siregar, Moammer Saddam Syahputra; Simanjuntak, Samuel Manutur (eJournal Kedokteran Indonesia, 2025)
As global populations age, the demand for orthopedic surgery continues to rise, with low back pain (LBP)—particularly due to herniated nucleus pulposus (HNP)—being one of the most common reasons for consultation and surgical intervention. However, surgical decisions in elderly patients are often complex due to clinical risks and comorbidities. This review examines the role of pharmacologic therapy as a first-line conservative treatment for HNP in older adults, focusing on the efficacy and safety of nonsteroidal anti-inflammatory drugs (NSAIDs), analgesics, opioids, antidepressants, anticonvulsants, and corticosteroid injections. NSAIDs such as ibuprofen, diclofenac, and etodolac are effective but pose risks of gastrointestinal, cardiovascular, and renal complications. Alternatives like paracetamol and metamizole offer better gastrointestinal tolerance, while tramadol is a preferred opioid because it carries a lower risk of dependence. Non-pharmacologic interventions—including physical therapy, acupuncture, moxibustion, and minimally invasive procedures like ozone chemonucleolysis—are also discussed as valuable adjuncts. While conservative management often results in significant symptom relief, prolonged reliance without timely surgical evaluation may lead to suboptimal outcomes. Therefore, a personalized, evidence-based approach that carefully balances risks and benefits is essential for optimizing outcomes and minimizing adverse effects in elderly patients with HNP.